Blue shoe - Lamott, Anne (Riverhead Books, 2003)
Mattie Ryder is a marvelously funny, well-intentioned, religious, sarcastic, tender, angry, and broke recently divorced mother of two young children. Then she finds a small rubber blue shoe, the kind you might get from a gumball machine and a few other trifles that were left years ago in her father's car. They seem to hold the secrets to her messy upbringing, and as she and her brother follow these clues to uncover the mystery of their past, she begins to open her heart to her difficult, brittle mother and the father she thought she knew. And with that acceptance comes an opening up to the possibilities of romantic love.